Effect of Planting Distance and Plant Population on Growth and Yields Sunflower (Helianthus annus L.): Pengaruh Jarak Tanam dan Populasi Tanaman Terhadap Pertumbuhan dan Hasil Tanaman Bunga Matahari (Helianthus annus L.) - Haryanta, Dwi; Susilo, Achmadi (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2024)
Planting sunflowers more densely was intended to maximize the use of nutrients, water and light so that you will get maximum results, but populations that were too dense or too low will not provide maximum results. The research aims to obtain the optimal planting distance and number of plants per hole to obtain high quantity and quality results. The research used a Randomized Completly Block Design (RCBD) factorial experiment consisting of two factors with the first factor being the planting distance in rows with four levels, namely J1 = 25 cm, J2 = 30 cm, J3 = 35 cm, and J4 = 40 cm, while the factor second is the plant population per planting hole (P) which consists of 2 levels, namely P1 = one plant per planting hole and P2 = two plants per planting hole. There were 8 experimental treatments which were repeated 3 times, arranged in a randomized completely block design. The research results concluded that there was no interaction between the plant spacing treatment factor and the number of plants per planting hole treatment factor for all research variables except plant height. The highest plant height value was at a shorter planting distance, namely 25-30 cm with one plant per planting hole. The variables number of leaves, flower diameter and flower weight had the highest values ​​in one plant per planting hole. For farmers who want to grow sunflowers, it was recommended to plant one plant per planting hole, the planting distance can be narrowed to get the ideal plant population.